Symbol

# Calculator search results

Formula
Solve the equation
Graph
$y = 3 x + 1$
$y = 2 \left ( 2 x - 1 \right )$
$x$Intercept
$\left ( - \dfrac { 1 } { 3 } , 0 \right )$
$y$Intercept
$\left ( 0 , 1 \right )$
$x$Intercept
$\left ( \dfrac { 1 } { 2 } , 0 \right )$
$y$Intercept
$\left ( 0 , - 2 \right )$
$3x+1 = 2 \left( 2x-1 \right)$
$x = 3$
 Solve a solution to $x$
$3 x + 1 = \color{#FF6800}{ 2 } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right )$
 Multiply each term in parentheses by $2$
$3 x + 1 = \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$3 x + 1 = \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ x } - 2$
 Simplify the expression 
$3 x + 1 = \color{#FF6800}{ 4 } \color{#FF6800}{ x } - 2$
$3 x + 1 = \color{#FF6800}{ 4 } \color{#FF6800}{ x } - 2$
 Move the variable to the left-hand side and change the symbol 
$3 x + 1 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } = - 2$
$3 x \color{#FF6800}{ + } \color{#FF6800}{ 1 } - 4 x = - 2$
 Move the constant to the right side and change the sign 
$3 x - 4 x = - 2 \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } = - 2 - 1$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ x } = - 2 - 1$
$- x = \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
 Find the sum of the negative numbers 
$- x = \color{#FF6800}{ - } \color{#FF6800}{ 3 }$
$\color{#FF6800}{ - } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 3 }$
 Change the sign of both sides of the equation 
$x = 3$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture